Remifentanil apnea: Case report and review of the literature - Nissar Shaikh; Yolande Hanssens; André Louon (Wolters Kluwer Medknow Publications, 2011)
Remifentanil is an opioid analgesic frequently used in intensive care patients because of its rapid onset of action, potency, and ultra-short duration. If an excessive dose is given, it leads to rapid, short lasting, potentially life-threatening side effects such as apnea, bradycadia, hypotension, and rigidity, following rapid peak serum levels. We report a 36-year-old woman developing apnea with bradycardia and hypotension, following an infusion in the central venous catheter lumen that had been used for remifentanil till tracheal extubation. The patient was immediately ventilated with bag-valve-mask and improved within 8 minutes. She became fully awake, heart rate and blood pressure returned to normal, and oxygen saturation improved to 100%. Acute care physicians, intensivists, anesthesiologists, and critical care nurses should be aware of this clinical problem in order prevent it as much as possible and to initiate immediate resuscitative measures.